Comparing the effects of positional versus myofascial release of gluteus medius to manage patellofemoral pain syndrome: single blinded randomized clinical trial - Kumar, Priyanka Ratan; Soomro, Rabail Rani (Journal of the Pakistan Medical Association, 2024)
Objective: To determine the effects of positional release technique in comparison to myofascial release technique on gluteus medius trigger point along with exercises to manage patellofemoral pain syndrome. Method: The single-blind, two-arm, randomised clinical trial was conducted at the Department of Physiotherapy, Sindh Institute of Physical Medicine, Karachi, from December 7, 2020, to March 24, 2021, and comprised patellofemoral pain syndrome of either gender with gluteus medius trigger point. They were randomly allocated to positional release technique group A and myofascial release technique group B. The intervention comprised 3 sessions per week for 6 weeks for a total of 18 sessions, with each session lasting 45 minutes. Function through anterior knee pain scale, pain through visual analogue scale, strength via hand-held dynamometer, and quality of life via World Health Organisation quality of life brief questionnaire were assessed alongside pressure pain threshold via algometer which was taken as the gluteus medius trigger point. All measurements were taken at baseline and 6 week post-intervention. Data was analysed using SPSS 21. Results: Of the 64 participants, 38(59.4%) were females and 26(40.6%) were males. There were 32(50%) subjects in group A with mean age 29.50+5.84 years and 32(50%) in group B with mean age 29.50+5.43 years (p>0.05). Both the groups showed a significant reduction in pain, improvement in function, pressure pain threshold, strength, and quality of life (p<0.05). Intergroup comparisons revealed no significant differences (p>0.05). Conclusion: Treating myofascial trigger points of gluteus medius muscle, using either positional release technique or myofascial release technique together with exercise therapy was found to be equally beneficial. ClinicalTrials.gov ID: NCT04667091 Key Words: Anterior knee pain, Exercise therapy, Trigger points, Manual therapy.